The Influence Of Work Environment And Emotional Intelligence On Employee Performance At PT. Agricinal Bengkulu Utara - Prananda, M Akbar; Irwanto, Tito; Nurzam, Nurzam (CV. Utami, 2026)
This study aims to determine the influence of work environment and emotional intelligence on employee performance at PT. Agricinal Bengkulu Utara, both partially and simultaneously. The background of this research stems from issues related to an unconducive work environment, high work pressure, and the low ability of some employees to manage emotions and maintain harmonious work relationships. The research uses a quantitative method with an associative approach. The population consists of 215 employees, with a sample of 140 respondents selected using the probability sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis with partial (t-test) and simultaneous (F-test) testing. The results showed that: (1) the work environment has a positive and significant effect on employee performance, as evidenced by the value of tcount 5.764 > ttable 1.656 and a significance level of 0.000 < 0.05; (2) emotional intelligence also has a positive and significant effect on employee performance with a tcount of 2.240 > ttable 1.656 and a significance level of 0.031 < 0.05; (3) simultaneously, the work environment and emotional intelligence significantly affect employee performance with an F significance value of 0.000 < 0.05. The questionnaire is valid for variable (X) because the calculated r value is greater than the table r value = 0.1648. The indicator that the question items in the questionnaire are valid is if the calculated r > table r. The table r, which is the fixed value, is 0.1648.